Upaya Hukum Perusahaan Untuk Bangkit Dari Jeratan Tuntutan Kepailitan - Putri, Fallen Annisa Aji (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2023)
The bankruptcy of a company has widespread negative impacts, both locally and globally. Therefore, the existence of bankruptcy institutions is crucial in the business world. These institutions enable the orderly and fair settlement of debts when a company can no longer compete or is forced to exit the market.Bankruptcy occurs when a debtor fails to pay debts that have fallen due and can be demanded, indicating an inability to pay or insufficient income to settle debts. Bankruptcy aims to resolve debt issues rather than intentionally destroy a business. The principle of